Comparison of pulmonary vein sizing by transesophageal echocardiogram and by direct angiogram. (8th February 2021) - Bachani, N; Vadivelu, R; Bagchi, A; Jadwani, JP; Panicker, GK; Shah, H; Dhirawani, B; Rathi, C; Lokhandwala, Y
Abstract: Funding Acknowledgements: Type of funding sources: None. Background: Pulmonary vein (PV) anatomy and sizing is important to know before performing PV isolation. This information is conventionally obtained by angiography or by CT scan. Aim: We undertook this study to identify and measure the PVs during TEE studies and validate these against angiography. Method: 17 consecutive patients due to undergo PV isolation for paroxysmal atrial fibrillation were analysed. Using TEE, the PVs were visualised (Upper panel) as follows: i) From the mid-esophageal four chamber view, the chamber probe was turned to the right at 110-130º for the bicaval view, where the RSPV was seen entering the left atrium adjacent to the SVC. ii) At 0º the SVC was imaged in its short axis, and the probe advanced till the interatrial septum was seen. The angle was changed to 30º to visualise the right inferior PV (RIPV). iii) From the two chamber view (70-90º), the probe was turned to the left and withdrawn to display the left superior PV (LSPV) entering the left atrium parallel to the appendage.iv) Keeping the LSPV in focus, the angle was changed to 135º and the probe advanced till the AV groove, where the left inferior PV (LIPV) was visualised. After transseptal puncture, each PV was cannulated. The PV angiograms were performed in several projections to obtain the best PV profile (lower panel). Using electronic callipers, each PV was measured within 1 cm of its entry into the left atrium, after having received all tributaries. Those PVs were considered for analysis which were measured by both TEE and angiography. The paired 'T' test was used to compare the PV diameters by TEE and angiography and the Bland Altman analysis was done to see the level of agreement. Results: Of a total of 68 PVs, 62 could be adequately visualised by TEE and 50 by angiography. These 50 PVs were measured using both methods. The diameters of the PVs measured by TEE and angiography were not statistically different by the paired t test; LSPV14 ± 1.8 mm v/s 14.4 ± 2.1 mm; RSPV 13 ± 1.8 mm v/s 14.6 ± 3.5 mm; LIPV 11.9 ± 2.1 vs 13.2 ± 2.8 mm and RIPV 10.5 ± 2.7 vs 12.1 ± 2.9 mm. Bland Altman analysis showed most PV sizes estimated by TEE and angiography lay within limits of agreement. Conclusions: A majority of PVs can be visualised by TEE using a defined protocol. TEE is a good technique to visualise and assess the size of PVs, avoiding the need for contrast medium and radiation.